Device-to-Device Communication as an Underlay in Coordinated Heterogenous Cellular Network - Chen Xu; Lingyang Song (Dianxin kexue)
Device-to-device（D2D）communication enables seamless operation of combining cellular and mobile Ad Hoc networks, which significantly improves the system spectrum efficiency and network capacity. The concept and application challenges of D2D local area network in theory and practice were introduced. The importance of cross layer resource management in solving interference avoidance of D2D communication was discussed, and an example of wireless resource management was also provided. The data results show that the performance of the proposed scheme is close to that of the exhaustive search optimal scheme, while has a relatively lower complexity. At present, D2D communication exhibits vast potential of achieving high system capacity and fully exploring wireless resources.